Alan W. Entwistle y Françoise Mallison (comps.). Studies in South Asian Devotional Literature: Research Papers, 1988-1991. Nueva Delhi: Manohar, 1994. xiv, 595 pp. - David N. Lorenzen (El Colegio de México, A.C., 1996)
-